Isolation, identification, and characterization of phosphate solubilizing bacteria, Paenibacillus sp., from the soil of Danum Valley Tropical Rainforest, Sabah, Malaysia - Herman Umbau Lindang; VIJAY KUMAR SUBBIAH; Kenneth Fransic Rodrigues; Cahyo Budiman (Society for Indonesian Biodiversity, 2021)
While phosphorus (P) is a vital element for the plant to grow, only 0.1% of the phosphate soil is directly to be uptake by plants. Consequently, P fertilizer, which is mostly taken from unrenewable resources of phosphate rock, is practically added into the croplands. Nevertheless, as the demand for this fertilizer kept increasing, the availability of resources and environmental issues are currently raising wide concerns. Alternatively, soil phosphate solubilizing bacteria (PSB) is promising to be further developed as a biofertilizer to increase the availability of P elements for plants. This study aims to screen and characterize novel PSB from the tropical rainforest soil. The soil samples were collected from the Danum Valley tropical rainforest, Sabah. Phosphatase solubilizing bacteria were then screened using the NBRIP Agar selective media. The screening results yielded five colonies, designated as PSB1, PSB2, PSB3, PSB4, and PSB5, displaying halos, with an average diameter of 10mm. Further, 16s rRNA gene sequence analysis using BLASTn suggested that PSB1, PSB2, PSB3, PSB4, and PSB5 were designated as Bacillus sp. PSB01, Pseudomonas oryzyhabitans PSB02, Staphylococcus pasteuri PSB03, Paenibacillus sp. PSB04, and Staphylococcus pasteuri PSB05, respectively. Interestingly, the Paenibacillus group is a promising biofertilizer and is currently used in the global agriculture industry. Accordingly, Paenibacillus sp. PSB04 was then selected for further characterization using Gram staining and observed under scanning electron microscope (SEM). The Gram staining revealed that Paenibacillus sp. PSB04 is a Gram-negative bacterium with a rod shape, which is in good agreement with the SEM result. The specific phosphatase activity of the extracellular fraction of this bacterium was 7378.12 U mg-1 which is the highest activity compared to previous studies. This study provides an early insight into an excellent phosphate solubilizing bacterium for the agriculture industry obtained from Danum Valley.